Microstructure and Hardness Properties of Ni-Si3N4 Composite Materials Produced by Powder Metallurgy Method - Houssain, Hasaneen; Islak, Serkan; Çalıgülü, Uğur (Kastamonu Üniversitesi, 2023)
In this study, the effect of the amount of Si3N4 on the microstructure and hardness properties of nickel (Ni) matrix silicon nitride (Si3N4) reinforced composite materials were investigated. Si3N4 was added to Ni at 5%, 10% and 15% by volume. The samples were produced using cold pressing and pressureless sintering technique. The sintering temperature was 1200 °C and the sintering time was 1 hour. SEM-EDS and XRD analyzes were used for the microstructure and phase formation analysis of the composites. The densities of the composites were measured according to the Archimedean principle. To determine the effect of Si3N4 on hardness properties, the microhardness of the samples was measured as Vickers. It was determined from XRD analysis that Ni, ?1 (Ni3Si) and ?-Ni3Si2 phases were formed in the microstructure. As the amount of Si3N4 increased, both the experimental densities and relative densities decreased, and the amount of pores partially increased. Due to the distribution strengthening effect of Si3N4 in the Ni matrix, there was an increase in the hardness values and the highest hardness was determined as 135 HV2 with the addition of 15% Si3N4.
Keywords: Mechanical Engineering (Other); Makine Mühendisliği (Diğer)